NAMA DAN MAKNA BAGIAN-BAGIAN PAKAIAN PENGHULU MINANGKABAU DI KENAGARIAN KACANG KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Amelia, Nadya; Manaf, Ngusman Abdul; Juita, Novia (Universitas Negeri Padang, 2017)
This article was written to ( 1) the name parts of moeslim leader’s uniform of Minangkabau ( 2 ) to explain the meaning of name ( symbol ) of each moeslim leader’s Minangkabau in Kabupaten Solok. This research is qualitative research that used descriptive method. The technical to gather this data with observation, interview and library studies. Analysis data do with grouping, syncronyzed, differenciate the data and eliminate to the others group but not syncrone and also gather the meaning. According this research found that the name parts of moeslim leader’s uniform Minangkabau in Kanagarian Kacang Kecamatan X Koto Singkarak Kabupaten Solok are: The head part is Saluak. The body part is baju hitam lapang, baju tidak bersaku, siba batanti/leher tidak berbuah, langan gadang, taburan banang emas, lilitan benang makau, cukia/ragi benang emas, motif pucuak rabuang. The trousers part is sarawa hitam gadang kaki. The accecories is Salempang, sisampiang, cawek, keris dan tungkek. The foot part is tarompa. Each name has a meaning leaders of the outfit, saluak symbolizes Minangkabau society is always consulted. Clothes and parts embodies the word leader is the result of collective consensus, the leaders are honest, patient, intelligent, and wise. Salempang implies sufficient in providing any prince in line with indigenous knowledge. Si sampiang and parts embodies the leaders knowledgeable and always helpful for others. Cawek meaning the leaders are patient and must protect its nephew. Keris symbolizes the tongue or speech of a leader. Tungkek/Stick meaning the elder person in a country and is obliged to maintain the prosperity of the country. Sarawa hitam gadang kaki implies that the prince always be on the right path and straight, and tarompa embodies a prince covered with kindness and all actions leaders must be resized. keywords: name, meaning, custom, Minangkabau